The Combined and Uneven Development of Afghan Nationalism. (December 2016) - Gopal, Anand
Abstract: The U.S. campaign in Afghanistan has been based, in part, on a pair of contradictory notions: First, that the Taliban are a supra‐ethnic, transnational group severed from the social and cultural heritage of Afghanistan; and second, that the Taliban represent a form of Pashtun nationalism. This article uses archival data and field research to show that both views are incorrect. The Taliban are historically rooted in Pashtun communities and yet are not a force of Pashtun nationalism. Rather, they comprise a network of exclusion, bound together in rhetoric by a particular conception of political Islam and Afghan sovereignty. This is an 'Islamist nationalism' in word, but crucially, not in deed: While the Taliban aspire to act as a nationalist force representing all Afghans, under conditions of institutional poverty and the lack of modernization, the Taliban are bound in practice by networks of trust and personal contact. This is an example of the 'combined and uneven development' of Afghan nationalism.